A rigidified AAZTA‐like ligand as efficient chelator for 68Ga radiopharmaceuticals. Issue 2 (12th February 2016) - Vágner, Adrienn; D'Alessandria, Calogero; Gambino, Giuseppe; Schwaiger, Markus; Aime, Silvio; Maiocchi, Alessandro; Tóth, Imre; Baranyai, Zsolt; Tei , Lorenzo
Abstract: The new cyclohexane‐fused CyAAZTA ligand was synthesized to increase the structural rigidity of the heptadentate chelator AAZTA with the aim of improving the overall stability of its Ga III complex. The stability constant of Ga(CyAAZTA) −, determined both by pH‐potentiometry (log K GaL =21.39) and by 71 Ga NMR (log K GaL =21.92), was found similar to that of GaAAZTA (log K GaL =22.18). The kinetic inertness of Ga(CyAAZTA) − was investigated by following its transmetallation and ligand exchange reactions with Cu 2+ and human serum transferrin, respectively. The formation of a hydroxido‐complex near pH 7 decreases the half‐life ( t 1/2 ) of the dissociation reactions for Ga(CyAAZTA) − compared to Ga(AAZTA) − (8.5 h vs 21 h, pH 7.4). However, at pH < 7 the t 1/2 of Ga(CyAAZTA) − is much longer (234 h at pH 6). Finally, CyAAZTA was successfully radiolabelled with 68 Ga in acetate buffer at pH 3.8, in 15 minutes at room temperature at [CyAAZTA]=10 μM, with a labelling yield higher than 80 %. A 1 μM solution of CyAAZTA was successfully labelled (L.Y.: 97.4 %) in 5 minutes at 90 °C. Stability tests in human serum and in the presence of 50 mM DTPA showed no significant decomposition of 68 GaCyAAZTA over 90 minutes. Abstract : A new rigid chelator based on a cyclohexane ring fused into an AAZTA‐like ligand was synthesized. The thermodynamic stability and kinetic inertness of the Ga III complex were investigated by pH potentiometry, 71 Ga NMR and UV‐spectrophotometry. The radiolabeling with 68 Ga was tested with different buffers, ligand concentrations and temperatures. Finally, the stability of 68 GaCyAAZTA was checked in human serum and with excess DTPA at 37 °C.